2022
DOI: 10.1073/pnas.2119415119
|View full text |Cite
|
Sign up to set email alerts
|

Species-specific KRAB-ZFPs function as repressors of retroviruses by targeting PBS regions

Abstract: Significance Hosts often target the relatively conserved regions in rapidly mutating retroviruses to inhibit their replication. One of these regions is called a primer binding site (PBS), which has to be complementary to the host tRNA to initiate reverse transcription. By analyzing endogenous retroviral elements, we found that host cells use this sequence as a target in efforts to block the expression of viral elements. A specific type of zinc finger protein targets the PBS in a host genome, which no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Additionally, it is unclear from our data what role repressive factors play in regulating HERV expression. Zinc finger proteins are known regulators of HERVs, via their ability to identify and bind motifs in the LTR and the PBS [ 57 59 ]. The KRAB-ZFPs have been reported to regulate DNA methylation and histone modification of HERVs through the recruitment of proteins such as KAP1/TRIM28 [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it is unclear from our data what role repressive factors play in regulating HERV expression. Zinc finger proteins are known regulators of HERVs, via their ability to identify and bind motifs in the LTR and the PBS [ 57 59 ]. The KRAB-ZFPs have been reported to regulate DNA methylation and histone modification of HERVs through the recruitment of proteins such as KAP1/TRIM28 [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it is unclear from our data what role repressive factors play in regulating HERV expression. Zinc finger proteins are known regulators of HERVs, via their ability to identify and bind motifs in the LTR and the PBS (Iouranova et al, 2022; Wolf et al, 2015; Yang et al, 2022). The KRAB-ZFPs have been reported to regulate DNA methylation and histone modification of HERVs through the recruitment of proteins such as KAP1/TRIM28 (Rowe et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In the field, an outstanding question is how different ERVs are targeted and repressed in physiological conditions. Although a few KRAB zinc-finger proteins such as ZFP809 and ZFP961 are identified for transcriptional silence of specific REs, other TFs remained to be determined (Imbeault et al, 2017; Tan et al, 2013; Wolf and Golf, 2009; Yang et al, 2022). In this work, we showed that POGZ binds to certain REs in a DNA sequence specific manner, analogous to KRAB zinc finger (KRAB-ZnF) proteins such as ZF809 and ZFP819.…”
Section: Discussionmentioning
confidence: 99%